Non-destructive observations of small crack using scanning laser-induced acoustic microscope - Atsuhiro KOYAMA (The Japan Society of Mechanical Engineers, 2016)
The scanning laser-induced acoustic microscope (SLAM) has been developed as a tool for non-destructive observations of the defects in materials. It consists of the laser with modulation system, the function generator, the lock-in amplifier, the AE sensor which detects the longitudinal acoustic waves, the XY stage and a computer for signal processing. The cyclic chopping laser beam causes the thermal wave. Our own-built SLAM has successfully provided some nondestructive observations; the bonding boundary of the different materials and the small crack in the materials. Since the SLAM senses the local difference of thermal properties in the sample, it performs observing the boundary or the crack well. The scanning laser-induced acoustic image (LAI) is affected by the power and chopping frequency of the laser. We revealed that the laser power more than a certain value (105 mW) is required in order to obtain a clear LAI with our SLAM in the case of the observation of aluminum alloy. Moreover, the LAI is affected by the chopping frequency of the laser and the LAI becomes clearer as the chopping frequency becomes higher even if the chopping frequency is up to 15 kHz which is relatively low.